Lipid Nanoparticle Delivery of siRNA to Osteocytes Leads to Effective Silencing of SOST and Inhibition of Sclerostin In Vivo - Genc Basha; Mina Ordobadi; Wilder R Scott; Andrew Cottle; Yan Liu; Haitang Wang; Pieter R Cullis (Elsevier, 2016)
Sclerostin is a protein secreted by osteocytes that is encoded by the SOST gene; it decreases bone formation by reducing osteoblast differentiation through inhibition of the Wnt signaling pathway. Silencing the SOST gene using RNA interference (RNAi) could therefore be an effective way to treat osteoporosis. Here, we investigate the utility of lipid nanoparticle (LNP) formulations of siRNA to silence the SOST gene in vitro and in vivo. It is shown that primary mouse embryonic fibroblasts (MEF) provide a useful model system in which the SOST gene can be induced by incubation in osteogenic media, allowing development of optimized SOST siRNA for silencing the SOST gene. Incubation of MEF cells with LNP containing optimized SOST siRNA produced significant, prolonged knockdown of the induced SOST gene in vitro, which was associated with an increase in osteogenic markers. Intravenous (i.v.) administration of LNP containing SOST siRNA to mice showed significant accumulation of LNP in osteocytes in compact bone, depletion of SOST mRNA and subsequent reduction of circulating sclerostin protein, establishing the potential utility for LNP siRNA systems to promote bone formation.